The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/2175-7860200960205
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura do sub-bosque lenhoso em ambientes de borda e interior de dois fragmentos de Floresta Atlântica em Igarassu, Pernambuco, Brasil

Abstract: RESUMO(Estrutura do sub-bosque lenhoso em ambientes de borda e interior de dois fragmentos de Floresta Atlântica em Igarassu, Pernambuco, Brasil) No intuito de avaliar a fisionomia, estrutura e o efeito de borda de um sub-bosque lenhoso, foram estudados dois remanescentes de Floresta Atlântica em Igarassu, Pernambuco (Mata do Pezinho -MPZ, 27 ha e Mata da BR -MBR, 99 ha). Para tanto, instalaram-se 10 parcelas de 5 × 5 m nas bordas (até 50 m da margem), interior I (50 -100 m) e interior II (> 300 m) em cada fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 36 publications
3
10
0
8
Order By: Relevance
“…Density in the understory of the outer edge area was lower than in the forest interior (6,320 versus 13,800 plants ha -1 respectively), a pattern similar to that reported by Silva et al (2008) in a 357 ha fragment (4,371 and 9,314 plants ha -1 respectively) and by Gomes et al (2009) in a 91 ha fragment (13,040 and 32,200 plants ha -1 respectively). The fact that the border environments had lower plant densities and greater mortalities (even while recruitment was similar to that seen in the interior) indicated that it had not stabilized and would require still more time to reach the values observed in the interior.…”
Section: Discussionsupporting
confidence: 87%
“…Density in the understory of the outer edge area was lower than in the forest interior (6,320 versus 13,800 plants ha -1 respectively), a pattern similar to that reported by Silva et al (2008) in a 357 ha fragment (4,371 and 9,314 plants ha -1 respectively) and by Gomes et al (2009) in a 91 ha fragment (13,040 and 32,200 plants ha -1 respectively). The fact that the border environments had lower plant densities and greater mortalities (even while recruitment was similar to that seen in the interior) indicated that it had not stabilized and would require still more time to reach the values observed in the interior.…”
Section: Discussionsupporting
confidence: 87%
“…Study design and data analysis -Initial surveys of the canopy and the woody understory of the "Mata de BR" forest were undertaken in the second half of 2005 by Lins-e-Silva (2010) and Gomes et al (2009) respectively. These authors defined the "edge" as extending up to 50 m into the fragment interior, followed by an "intermediate" environment extending from 50 to 100 m farther in, with the "interior" forest environment being more than 150 m from the forest edge.…”
Section: Methodsmentioning
confidence: 99%
“…Considerando que a literatura relata que distúrbios estocásticos locais podem desencadear a expansão da densidade (Harper et al, 2005) supõe-se que a maior densidade no interior de Vespas ocorreu em função, provavelmente, de um distúrbio local que, por sua vez, favoreceu a população de Eschweilera ovata amostrada com um elevado número de indivíduos naquele ambiente. Vale a pena destacar que maior densidade no interior foi um comportamento generalizado nos remanescentes da Usina São José, com cerca de 400 ha (Silva et al, 2008a, Silva, 2010 ou em torno de 100 ha (Gomes et al, 2009, Mendes, 2010. Destaca-se que esses autores afirmaram não haver registro visual de corte nas áreas.…”
Section: Coleta E Tratamento De Dadosunclassified
“…A maior riqueza no interior nega a hipótese deste trabalho. Trata-se de um padrão encontrado em outros remanescentes da Usina São José, independente de seu tamanho (Silva et al, 2008a;Gomes et al, 2009). Tais resultados apontam que, independente do tamanho do remanescente, o ambiente interior parece ser apropriado para o estabelecimento de novas plantas, que o ambiente de borda.…”
Section: Dinâmica Geralunclassified